Membangun Perencanaan dan Kinerja Tim: Analisis Pengaruh Efikasi Kolektif dan Iklim Kecerdasan Emosional - Dewiana Novitasari; Dhaniel Hutagalung; Nelson Silitonga; Muhammad Johan; Masduki Asbari (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2021)
This study postulates team characteristics and environmental factors as the main drivers of team performance. In the proposed model of this study, team performance is positively and significantly affected by collective efficacy and emotional intelligence climate. Likewise, team planning has a positive and significant effect on team performance. Data werecollected from 103 of sales/marketing employees of a manufacturing industry in Indonesia by random sampling. Data were analyzed using SEM method with SmartPLS 3.0 software. The results of this study indicated that collective efficacy and emotional intelligence climate have a positive and significant effect on team planning and team performance. Likewise, team planning has a positive and significant effect on team performance. Moreover, the empirical test of this study, by investigating sales/marketing employees working in the Indonesian manufacturing industry, complements the application of social cognitive theory in understanding team performance. Finally, the managerial implications of team performance and future open problems are discussed at the end of the research report.